Use of shopee paylater features in consumptive behavior of Bengkulu University students - M. Dimas Hasmikhori; Kamaludin Kamaludin (Institute of Computer Science (IOCS), 2024)
In the current era of globalization, online businesses are increasingly gaining attention among students, there are many types of online shopping e-commerce, one of which is popular is Shopee PayLater. With the convenience and attractive offers provided by Shopee, this encourages students to engage in consumer behavior. The aim of this research is to find out the consumer behavior of Bengkulu University students in using Shopee PayLater, and to find out what Bengkulu University students think about using the Shopee PayLater feature. This research uses a qualitative phenomenological approach. Data collections techniques are carried out through interviews, documentation, literature study. The results of this research are that there are several things that show the consumptive behavior of Bengkulu University students, namely shopping to maintain their appearance, shopping because of discounts, shopping because they follow fashion trends, shopping because they are influenced by advertising. The students' opinions from this research are that there are positive and negative experiences they had while using Shopee PayLater. The suggestion in this research is that female students must also learn to manage their finances and learn to restrain themselves from prioritizing desires over needs.